Histochemical and immunohistochemical differences between solitary oral fibroma and fibrous papule of the face - Águida Cristina Gomes Henriques; Roseana de Almeida Freitas; Bruno Cunha Pires; Clarissa Araújo Gurgel; Jean Nunes dos Santos (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Background: The morphological similarities between fibrous papules of the face and multiple sporadic oral fibromas were mentioned long ago and a relationship between them has been reported in the literature. Objective: The aim of this study was to evaluate the participation of mast cells, elastin and collagen in a series of oral fibromas and fibrous papules of the face in order to better understand the possible role of these factors in fibrosis and the formation of these lesions. Methods: Thirty cases of oral fibroma involving the buccal mucosa and 30 cases of fibrous papules of the face were selected. Tissue samples were submitted to picrosirius red staining and immunohistochemistry using anti-elastin and anti-tryptase antibodies. Results: The percentage of tryptase-positive mast cells and expression of elastin were higher in cases of fibrous papules of the face (p < 0.05). In contrast, a higher intensity of collagen deposition was observed in oral fibromas. The results showed mast cell accumulation and higher elastin synthesis in fibrous papules of the face, and mast cell accumulation with higher collagen fiber synthesis in oral fibromas. Conclusion: These findings support the hypothesis that mast cells influence the development and growth of these lesions through different mechanisms.